CHALLENGES FACED BY SPECIALISTS IN TREATING CHILDREN WITH INTERMITTENT EXPLOSIVE DISORDER: CAUSES AND CONSEQUENCES - Rodrigues, Erika Camilo; Fagundes, Fabiana; da Silva, Fabiana Ferreira; Spilla, Juliana Fernanda de Moraes; dos Santos, Jéssica Aparecida de Oliveira; Quintino, Máyra Patrícia Camargo; Sanchez, Rosana Cristina Rossler; Gomes, Viviane Luzia Bruceze (Seven Editora, 2026)
Intermittent Explosive Disorder (IED) is characterized by recurrent episodes of aggression and anger outbursts disproportionate to the situation experienced. In the educational and clinical context, specialists face several challenges when dealing with children diagnosed with or showing signs of this disorder. This article aims to discuss the main difficulties faced by professionals in monitoring these children, as well as to present possible causes and consequences of this disorder in child development. The research is based on a literature review on child behavior, emotional regulation, and impulse control disorders. It is observed that the lack of institutional preparation, the lack of knowledge about the disorder, and the emotional complexity of children are factors that hinder the specialist's work. It is concluded that interdisciplinary monitoring, combined with adequate professional training and family support, is fundamental for the healthy development of the child.